Current developments in lipid-lowering therapy for the patient with chronic kidney disease. (December 2011) - Burnhope, Emma; Green, Darren; Kalra, Philip A; Kalra, Paul R
Cardiovascular disease is the leading cause of death amongst patients with chronic kidney disease, particularly end-stage disease. Patients with chronic kidney disease commonly exhibit abnormalities of lipid profile, but also atypical cardiovascular risk factors such as arterial stiffness and chronic inflammation. Hence it is unclear whether these patients benefit from lipid-lowering therapy to the same degree as the general population. In this review we discuss evidence on the clinical benefit and safety of lipid-lowering agents for different stages of chronic kidney disease.